PRESENTATION OF PARADIGMATIC MODEL OF TOURISM ECONOMY USING GROUNDED THEORY - Salehabadi, Reyhane; Mottaghi, Afshin; Seifi, Anahita; Pletnev, Dmitri (ВЕСТНИК ЧЕЛЯБИНСКОГО ГОСУДАРСТВЕННОГО УНИВЕРСИТЕТА; № 2(436) (2020): Вестник Челябинского государственного университета, 2022)
Today, tourism industry has enjoyed noticeable potential for producing wealth and increasing revenue to various countries so that it is able to devote an important part of Gross Domestic Product (GDP) in pioneering countries involved in in this industry. Thus, tourism is assumed as one of the key and strategic factors for economic growth and development of the nations. The current research has been written qualitatively in order to identify the influential dimensions and elements in tourism economy and using method of Grounded Theory. The statistical population of this study includes professors and experts were totally 14 subjects in the field of tourism economy. The research findings indicate that the final model for tourism economy comprises of 16 major categories and 107 minor issues. These categories include contextual factors (infrastructural, political- legal, sociocultural, environmental and investment), causal factors (culture-building in community, training of general and individual skills, and geographic positions and situations), consequences (analysis on economic factor, demand- and- supply analysis, regional balance, price of goods and lands, and sociocultural dimensions), and strategies (determination of educational and research strategies, strategic insight and codification of mission and macro goals). As a result it can be implied that tourism economy is a multidimensional phenomenon that is formed systematically by different factors and elements. Therefore, all these factors should be addressed and emphasized as whole to exploit from these existing advantages and potentials in such type of tourism.   DOI:  https://doi.org/10.24411/1994-2796-2020-10212